DEVELOPMENT OF AN INFORMATION SYSTEM FOR ATTENDANCE AND STUDENT PROGRESS AT PAUD TUNAS MUDA - Muhammad Ghazali; Arif Pramudwiatmoko (Jurnal Riset Informatika, 2025)
The Tunas Muda Early Childhood Education Student Attendance and Progress Recording Information System application is a digital platform designed to help teachers record student attendance and progress in a modern and efficient manner. Currently, the recording process is still done manually, causing various obstacles such as late reporting, data inaccuracy, and difficulties in comprehensively monitoring student progress. This research uses the Research and Development (R&D) method. The purpose of this research is to develop a system that can facilitate teachers in taking attendance and recording student progress and enable school principals to monitor attendance and progress data through graphical displays and statistical analysis. Data collection was conducted through direct interviews with teachers as the main users. The system was developed using Flutter SDK for the interface and Firebase Firestore as the database. The results of the study show that the application is capable of recording student attendance and progress in real time, generating reports in PDF format, and displaying attendance and progress analysis in an informative graphical form.